Ionophoric properties of a tetra-tetrazole functionalised calix[4]arene - D'Alessio, Daniel; Skelton, B.; Lengkeek, N.; Fraser, B.; Krause-Heuer, A.; Muzzioli, S.; Stagni, S.; Massi, Max; Ogden, Mark (2015)
© 2015 Taylor & Francis. The synthesis and characterisation of p-t-butylcalix[4]arene functionalised at the lower rim with four tetrazole moieties is reported. The macrocycle is found to be a poorer ionophore for lanthanoid cations than the bis-tetrazole-substituted analogue. Solution-phase photophysical studies strongly suggested that the cations interacted only weakly with the calixarene ligand. A mixed sodium/triethylammonium salt of the calixarene ligand was crystallised in the presence of lanthanoid cations and structurally characterised. Strong intramolecular interactions are hypothesised to be the cause of the observed behaviour.